Pengaruh Kualitas Produk dan Store Atmosphere Toko terhadap Keputusan Pembelian Ice Cream Mixue pada Mahasiswa Universitas Negeri Medan - Hutagalung, Gracella Rosnah S; Aprinawati, Aprinawati; Lubis, Adelina; Wulandari, Artika (Journal of Management Accounting, Tax and Production, 2025)
The purpose of this study is to investigate how Universitas Negeri Medan students' shopping decisions  Toko Mixue Pancing are influenced by product quality and store atmosphere.  Product quality is an important factor in making customers satisfied, while the store atmosphere contributes to a comfortable and enjoyable shopping experience.  This quantitative study uses associative and descriptive approaches, and 80 respondents are students from Universitas Negeri Medan.  Multiple linear regression analysis was used after the data was collected through a Likert scale questionnaire.  The research results show that product quality has a positive and significant impact on purchasing decisions, with a t-value of 4.469 greater than the t-table value of 1.990 and a significance value of 0.001 0.05.  The warehouse atmosphere also has a positive influence, with a t-value of 4.211 greater than the t-table value of 1.990 and a significance value of 0.001 0.05.  Furthermore, the F-test results indicate that both independent variables simultaneously influence purchasing decisions, with a calculated F value of 60.443 greater than the table F value of 3.12 and a significance level of 0.001 lower than 0.05.  The quality of the product and the store environment account for 61.1% of the differences in students' purchasing decisions, according to a coefficient of determination (R2) of 0.611.  Therefore, improving product quality and optimizing the store environment can be an effective strategy to enhance customer attraction and loyalty.  This research provides the managers of Mixue Pancing Store with information that they can use to enhance their competitiveness in the beverage and ice cream market.